2022
DOI: 10.1038/s41467-022-30979-0
|View full text |Cite
|
Sign up to set email alerts
|

Excess ribosomal protein production unbalances translation in a model of Fragile X Syndrome

Abstract: Dysregulated protein synthesis is a core pathogenic mechanism in Fragile X Syndrome (FX). The mGluR Theory of FX predicts that pathological synaptic changes arise from the excessive translation of mRNAs downstream of mGlu1/5 activation. Here, we use a combination of CA1 pyramidal neuron-specific TRAP-seq and proteomics to identify the overtranslating mRNAs supporting exaggerated mGlu1/5 -induced long-term synaptic depression (mGluR-LTD) in the FX mouse model (Fmr1−/y). Our results identify a significant increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 88 publications
(116 reference statements)
2
7
0
Order By: Relevance
“…These data are corroborated by previous Ribo-tag studies of Fmr1 KO hippocampal cells, which similarly showed that 11/12 differentially expressed FMRP targets are reduced rather than increased in expression ( Ceolin et al 2017 ). Our findings here are similarly consistent with observations that FMRP CLIP targets have concordantly reduced ribosome footprints ( Das Sharma et al 2019 ), that FMRP preferentially binds to long transcripts ( Sawicka et al 2019 ; Li et al 2020 ), and that the protein levels of large proteins are reduced rather than increased in the Fmr1 KO hippocampal proteome ( Seo et al 2022 ). Our data are also consistent with other prior reports that FMRP activates the translation of its targets ( Bechara et al 2009 ; Tabet et al 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…These data are corroborated by previous Ribo-tag studies of Fmr1 KO hippocampal cells, which similarly showed that 11/12 differentially expressed FMRP targets are reduced rather than increased in expression ( Ceolin et al 2017 ). Our findings here are similarly consistent with observations that FMRP CLIP targets have concordantly reduced ribosome footprints ( Das Sharma et al 2019 ), that FMRP preferentially binds to long transcripts ( Sawicka et al 2019 ; Li et al 2020 ), and that the protein levels of large proteins are reduced rather than increased in the Fmr1 KO hippocampal proteome ( Seo et al 2022 ). Our data are also consistent with other prior reports that FMRP activates the translation of its targets ( Bechara et al 2009 ; Tabet et al 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…We examined the protein expression profiles of mature hiPSC‐ and hESC‐astrocytes using LC–MS and identified several dysregulated pathways using IPA. Some of our findings, such as dysregulated ribosomes and altered translation while expected based on the literature (Li et al, 2020; Seo et al, 2022), are still novel as shown here for astrocytes specifically. However, the proteomic analysis also pointed towards novel, previously unappreciated changes in FXS astrocytes which we have validated.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, we speculate that an increase in the expression of these transcripts translates into a higher ribosome loading, which is consistent with the observation of increased eIF4E-eIF4G interactions resulting from the loss of FMRP. Alternatively, it may reflect an imbalance in the translation of long versus short length mRNAs 81 .…”
Section: Discussionmentioning
confidence: 99%